Dissociating contributions of the motor cortex to speech perception and response bias by using transcranial magnetic stimulation - Smalle, Eleonore H.M.; Rogers, Jack; Möttönen, Riikka (Oxford University Press, 2015)
Recent studies using repetitive transcranial magnetic stimulation (TMS) have demonstrated that disruptions of the articulatory motor cortex impair performance in demanding speech perception tasks. These findings have been interpreted as support for the idea that the motor cortex is critically involved in speech perception. However, the validity of this interpretation has been called into question, because it is unknown whether the TMS-induced disruptions in the motor cortex affect speech perception or rather response bias. In the present TMS study, we addressed this question by using signal detection theory to calculate sensitivity (i.e., d′) and response bias (i.e., criterion c). We used repetitive TMS to temporarily disrupt the lip or hand representation in the left motor cortex. Participants discriminated pairs of sounds from a “ba”–“da” continuum before TMS, immediately after TMS (i.e., during the period of motor disruption), and after a 30-min break. We found that the sensitivity for between-category pairs was reduced during the disruption of the lip representation. In contrast, disruption of the hand representation temporarily reduced response bias. This double dissociation indicates that the hand motor cortex contributes to response bias during demanding discrimination tasks, whereas the articulatory motor cortex contributes to perception of speech sounds.